Modelo conceptual para la distribución de mercancías en las nanostore pertenecientes a la zona suroccidente de Barranquilla (2023)
This exploratory and descriptive research study presents a conceptual model that describes the merchandise distribution channel in the nanostore or traditional neighborhood stores that belong to the southwestern side of the city of Barranquilla-Colombia, applying the kilometer methodology. square (Km2) by means of which we show the total operability in order to carry out an analysis of the method used by the neighborhood stores for their supply, thus suggesting alternative methods for the improvement of their distribution. We descriptively characterize the main and fundamental factors of this process, among themselves; how the demand is generated, how the order is processed, the payment of the order, how is the physical distribution and finally the service after the sale or post-sale. In order to meet our objective, a survey was applied as a data collection tool to 256 nanostores in the southwestern town of Barranquilla; applying statistical methods to the information collected.